A Natural Stress Deflector on the Head? Mechanical and Functional Evaluation of the Woodpecker Skull Bones. Issue 4 (29th January 2019) - Jung, Jae‐Young; Pissarenko, Andrei; Trikanad, Adwait A.; Restrepo, David; Su, Frances Y.; Marquez, Andrew; Gonzalez, Damian; Naleway, Steven E.; Zavattieri, Pablo; McKittrick, Joanna
Abstract: The brain is one of the most important and complicated organs, but it is delicate and therefore needs to be protected from external forces. This makes the pecking behavior of the Woodpecker so impressive, as they are not known to sustain any brain injury due to their anatomical adaptations (a specialized beak, skull bone, and hyoid bone). However, the relationship between the morphology of the woodpecker head and its mechanical function against damage from daily pecking habits remains an open question. Aided by recent technical advancements, these questions can be explored by applying new materials science concepts of bioinspiration and bioexploration to identify adapted structures/materials in a design that results from millions of years of evolution. Two main features, including the beam‐like bar structure of the jugal bone acting as a main stress deflector and the high natural frequency of the skull bone of woodpeckers can teach two lessons for potential materials development as well as engineering applications: protection of a delicate internal organ occurs by redirection of the main stress pathway and a large mismatch of the natural frequencies between the skull and brain avoids resonance and reduces the overall load experienced by the brain. Abstract : The relationship between the morphology of the woodpecker head and its mechanical function against damage from daily pecking habits is explored: the beam‐like bar structure of the jugal bone acts as a main stress deflector and the high natural frequency of the skull bone of woodpeckers allows to avoid resonance between the skull bone and brain.